Nitrogen-doped bcc-Cr films: Combining ceramic hardness with metallic toughness and conductivity. (September 2016) - Greczynski, G.; Lu, J.; Tengstrand, O.; Petrov, I.; Greene, J.E.; Hultman, L.
Abstract: We report the first results on nanostructured N-doped bcc -Cr films exhibiting the unique combination of ceramic hardness with metallic toughness and electrical conductivity at unexpectedly low N concentrations, 5 at.%. The Cr:N films are deposited at 200 °C in N2 /Ar mixtures by high-power pulsed magnetron sputtering using tunable time-domain control of Cr + and Cr 2+ ion fluxes incident at the film growth surface. Subplanted N atoms impede annealing of metal-ion induced point defects and hinder bcc -Cr grain growth, resulting in a material with a nearly isotropic nanostructure and atomically smooth surface, rather than typical Cr:N solid solutions consisting of faceted microcolumns. Graphical abstract: